Invasive pulmonary aspergillosis in a COVID-19 recovered patient: unravelling an infective sequalae of the SARS-CoV-2 virus - Shadrach, Benhur Joel; Goel, Rishabh; Deokar, Kunal; Jain, Anukool (Monaldi Archives for Chest Disease, 2021)
Dear Editor, A 55-year-female, house wife, non-smoker, morbidly obese (BMI>35) with no other co-morbidities or pre-existing lung disease presented to the emergency room with complaints of highgrade fever, cough with minimal sputum, progressive breathlessness, streaky haemoptysis, and anorexia for the past 5 days. She was admitted in intensive care unit (ICU) for severe COVID-19 pneumonia three months back and had successfully recovered after 24 days of hospitalization....